2022
DOI: 10.3389/fonc.2022.869390
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of T790M Acquisition After Treatment With First- and Second-Generation Tyrosine-Kinase Inhibitors: A Systematic Review and Network Meta-Analysis

Abstract: BackgroundLung adenocarcinoma is a common disease with a high mortality rate. Epidermal growth factor receptor (EGFR) mutations are found in adenocarcinomas, and oral EGFR-tyrosine kinase inhibitors (EGFR-TKIs) show good responses. EGFR-TKI therapy eventually results in resistance, with the most common being T790M. T790M is also a biomarker for predicting resistance to first- and second-generation EGFR-TKIs and is sensitive to osimertinib. The prognosis was better for patients with acquired T790M who were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The results of our study indicated that bevacizumab in addition to 1st/2nd-generation EGFR-TKIs does not alter the mechanism of acquired resistance in advanced primary EGFR-mutated NSCLC. Some previous studies showed that prior afatinib therapy was associated with a lower secondary T790M mutation-positive rate when compared with first-generation EGFR-TKIs, and these results were similar to those in our study ( 23 , 24 ). Some previous studies showed that prior afatinib therapy was not associated with a lower secondary T790M mutation-positive rate and that this rate was even higher than that for first-generation EGFR-TKIs ( 25 , 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study indicated that bevacizumab in addition to 1st/2nd-generation EGFR-TKIs does not alter the mechanism of acquired resistance in advanced primary EGFR-mutated NSCLC. Some previous studies showed that prior afatinib therapy was associated with a lower secondary T790M mutation-positive rate when compared with first-generation EGFR-TKIs, and these results were similar to those in our study ( 23 , 24 ). Some previous studies showed that prior afatinib therapy was not associated with a lower secondary T790M mutation-positive rate and that this rate was even higher than that for first-generation EGFR-TKIs ( 25 , 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, 80% of patients with EGFR T790M positive mutations were found to get an exon 20 acquired resistance mutation C797S (nucleophilic CYS becomes hypersensitive SER) at the site of drug binding after about 12 months of treatment with Osimertinib, 33 which led to the resistance to Osimertinib. Therefore, it is necessary to develop new and more effective EGFR inhibitors.…”
Section: Introductionmentioning
confidence: 99%